Order Diptera Linnaeus, 1758. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Pape, Thomas; Blagoderov, Vladimir; Mostovski, Mikhail B. (Zootaxa, 2011)
-